Croatian approach to human rights / democratic citizenship education - Spajić-Vrkaš, Vedrana (2001)
The presentation will focus on the possibilities and obstacles in strengthening democracy and civil society in Croatia in the context of implementing and further developing Croatian national Human Rights Education Programme. The Programme is built on the notions of synergy, partnership and shared responsibilities, both in relation to defining and implementing the aims, contents and methods of teaching and learning, as well as evaluating the outcomes, by taking into account all possible social partners at local, national and international levels. The purpose is to integrate different existing approaches (democratic citizenship education, civic education, peace education, intercultural education, tolerance education, global education, and the like) into a coherent whole under an umbrella of human rights education and to use all possible human resources in promoting knowledge, skills, values and commitments of children and youth to grasp the challenges of a post-communist and post-war democratic development through the promotion of, respect for, and protection of universal human rights and freedoms. The national Programme originated from the UNESCO sponsored project on Peace and Human Rights for Croatian Primary Schools run from 1997-1999 that developed a conceptual basis for human rights life-long learning, a lower elementary grades programme and key materials for teaching and learning in that field. A joint action of the Project team, National Human Rights Education Committee and the Human Rights Education Associates from U.S. resulted in a series of teacher training seminars with a view to prepare the teachers for efficient implementation of the national Programme. Despite an observable enthusiasm that permeates schools implementing the national Human Rights Education Programme, there are many obstacles that need to be properly accessed and removed in order to reach the level at which the synergy, partnership and shared responsibilities will be fully and satisfactorily exercised. Some of the obstacles defined in the course of a focus-group study on the implementation of education for democratic citizenship policy under the auspices of the Council of Europe last July, will be presented at the Seminar, as well as the ideas on how these obstacles may be removed. It will be pointed out that the strengthening of civil society through the implementation of human rights education programmes depends on the possibility for dialogue and exchange of ideas and practices not only among individual citizens but among all institutions and organisations of a democratic society at local, national and international levels. Participation, interaction, transparency and responsibility/accountability are to be achieved through education if clear priorities, approaches, strategies and roles are set up that reflects the respect for human dignity and the care for shared values and objectives of social development.